The Politics of the Electoral Act Amendment and the 2019 General Elections in Nigeria - Oluwashina Moruf Adebiyi; Joseph Oludare Olowa (Modern Africa)
Amending the 2010 Electoral Act before Nigeria’s 2019 general elections generated huge controversies. The determination of the legislature to get the Electoral Act amended and the refusal of the executive to grant assent to the Electoral Bill raises the question: In whose interest was the proposed amendment? The present article examines the political issues that surrounded the amendment of the Electoral Act vis-à-vis the 2019 elections in Nigeria. The article argues that the electoral amendment bill may not after all be in the interest of a credible election as each political party tried to manipulate the bill and the process of amendment to its advantage. The article is qualitative and theoretical and adopts the thematic analysis to draw contextual inferences. It also adopts the cartel party theory.